Web resources as support in nursing education - Marletta, Giuseppe; Camposano, Gilda; La Torre, Pasquale; Romano, Rita; Cona, Alex; Tornambè, Filippo; Ferrari, Luciano; Trani, Serena (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Social media have become an integral part of daily life for individuals of all ages, including university students. They are not only used for social purposes but can also be integrated into education, expanding methodology and enhancing learning. The aim of the study was to analyse the role that Web 2.0 resources play in the learning process of nursing students. Methods: An observational study was conducted using a validated questionnaire, administered to a sample of 104 students from the University of Parma, specifically from the Faculty of Nursing, including first, second, and third-year students. Results: The study revealed that the majority of students use visual resources from the web to learn nursing procedures, with a strong preference for video resources from the YouTube® platform. Discussion and conclusion: This study highlighted the significant potential of audio-visual content, which can be effectively utilised to expand learning methodologies for clinical and nursing procedures within the university setting. In the future, it would be interesting to propose the creation of a dedicated YouTube® channel at the University of Parma, where self-produced nursing-related material could be shared, as well as further investigate the topic from the perspective of the teaching staff.